Pertanggung Jawaban Pidana Dalam Tindak Pidana Korupsi Yang Dilakukan Oleh Hakim - Ahmad Yunus; Moh. Jeweherul Kalamiah (Hakim: Jurnal Ilmu Hukum dan Sosial, 2023)
Judges are often referred to as God's representatives in the world, this is because of the extraordinary role of judges in overseeing the law and upholding justice, including in eradicating criminal acts of corruption. As time goes by, the disease of corruption has not only infected ordinary officials, but even officials tasked with law enforcement, in this case judges, have also been caught in cases of criminal acts of corruption. Of course, this is not a trivial problem, where a judge who is supposed to uphold legal norms in order to achieve justice and peace in society, instead commits a criminal act of corruption. The criminal act of corruption is a criminal act that falls into the category of extra ordinary crime, this is because the impact of this criminal act of corruption is very large and systematic. Therefore, the state, in this case represented by the government, must make special breakthroughs in responding to judges who commit criminal acts of corruption, of course one of which is by using criminal law instruments which contain penalties. The punishment of criminals whose status is an ordinary person should not be equated with those whose status is a state official, in this case a judge. In this legal matter, the state must really show its teeth to prove to the public that law enforcement in Indonesia is not only sharp downwards but also sharp upwards. In this research the author will discuss criminal responsibility in criminal acts of corruption committed by judges.